SEASONAL DYNAMICS OF ENVIRONMENTAL VARIABLES AND ZOOPLANKTON STRUCTURE IN WASTEWATER RESERVOIRS OF THE RIGHT-BANK SORBULAK CANAL SYSTEM (Experimental biology, 2022)
The annual increase in wastewater volumes necessitates comprehensive studies of water bodies subsidized by anthropogenic activities. An example of such reservoirs is Sorbulak and a system of shallow ponds into which pre-treated wastewater from Almaty and its environs is discharged. The published works provide fragmentary data on the hydrochemical and hydrobiological regimes of Sorbulak and ponds. There is no information on the seasonal dynamics of these variables. Our paper, aimed at studying the seasonal dynamics of pollutants and the zooplankton structure, partially fills this gap. Environmental and biological samples were taken in Sorbulak and two ponds by standard methods once a month, from April to September of 2021. The content of nutrients was high, and the heavy metals concentrations, except for copper, were low. The seasonal dynamics of pollutants in reservoirs were determined mainly by their entry from wastewater, with a more negligible contribution of natural factors. Zooplankton was represented by 80 species with an average abundance of 177.3-834.4 thousand ind./m3 and average biomass of 9.6-10.4 g/m3. The values ​​of the Shannon index were 1.98-2.12 bit/ind and 0.88-1.76 bit/mg, the average mass of an individual was 0.0140-0.0853 mg. The seasonal dynamics of zooplankton in the surveyed water bodies were different. The obtained results and comparison with the data of previous studies testified to the instability of the species composition of zooplankton communities both during one year and in individual years. Contradictions between the structure of zooplankton communities and the chemical variables of the studied reservoirs were identified. The results obtained to make a theoretical and practical contribution to understanding the formation of water quality in reservoirs with mixed pollution emphasize the need for further comprehensive studies of reservoirs of this type, and show specific differences between anthropogenic and natural successions of aquatic ecosystems.